2012
DOI: 10.1093/ejcts/ezs560
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interstitial lung disease on short-term and long-term survival of patients undergoing surgery for non-small-cell lung cancer: analysis of risk factors

Abstract: In conclusion, major lung resection in patients with NSCLC and ILD is associated with an increased postoperative morbidity and mortality. Patients with a low preoperative FVC% should be carefully assessed prior to undergoing surgery, particularly in the presence of a lower DLCO%. Long-term survival is significantly lower when compared with patients without ILD, but still achievable in a substantial subgroup. Thus, surgery can be offered to properly selected patients with lung cancer and ILD, keeping in mind th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 23 publications
(45 reference statements)
4
48
2
Order By: Relevance
“…Our results also differed from the other studies that included only lung resection surgeries and reported lower preoperative FVC% and D LCO % in association with PPCs [11,16]. Moreover, the results differed from those in chronic obstructive pulmonary disease patients that showed increased incidence of PPCs according to underlying pulmonary function [18,19,20].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also differed from the other studies that included only lung resection surgeries and reported lower preoperative FVC% and D LCO % in association with PPCs [11,16]. Moreover, the results differed from those in chronic obstructive pulmonary disease patients that showed increased incidence of PPCs according to underlying pulmonary function [18,19,20].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have shown that other types of ILD also influence PPCs and mortality after lung surgery [10], and the patients with ILD had a higher incidence of these complications compared to those without ILD after lung resection. Among all types of PPCs, acute respiratory distress syndrome was reported at a significantly higher percentage in ILD patients versus those without ILD (13.5 vs. 2.3%), and mortality was also higher in the patients with ILD (8.1 vs. 1.4%) [11]. However, there is little published data focusing on the incidence and characteristics of PPCs after surgery other than lung surgery in patients with ILD.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It has been reported that the presence of ILD increased the incidence of postoperative acute respiratory distress syndrome and acute exacerbations [17][18][19] and that ILD was a poor prognostic factor after surgery. [20][21][22][23][24] Thus, lung cancer patients with ILD are not good candidates for surgical resection. Because of its less invasive nature, SBRT for stage I NSCLC is mostly performed in patients with comorbidities-patients with ILD are sometimes considered for SBRT.…”
mentioning
confidence: 99%
“…Several proteins upregulated in IPF are directly involved in carcinogenesis and lung areas of active fibrosis may represent potential targets in vivo 31: 773-777 (2017) of lung neoplasms (13,23). In IPF patients, invasive diagnostic procedures, as well as surgical or pharmacological treatments may induce acute exacerbation and increased mortality (19,20,22).…”
Section: Discussionmentioning
confidence: 99%
“…A perioperative Pirfenidone treatment has recently been proposed to reduce the incidence of postoperative acute events (18)(19)(20). In this context, the therapeutic management of LC is a difficult task and is still questioned, especially in IPF patients with severe fibrotic involvement, whether the tumor should be treated or not (21,22). Although Lee et al (15) reported that radiotherapy and surgical treatments of LC result in a reduced survival of IPF patients, according to Kumar et al (19) lung resection in selected cases can improve their survival.…”
mentioning
confidence: 99%